Eksplorasi Up-Cycle Sampah dengan Pendekatan STEAM-Tri N untuk Peningkatan Kreativitas Siswa - Fajar Arum Sari; Moh Rusnoto Susanto; Insanul Qisti Barriyah; Ana Fitrotun Nisa; Heri Maria Zulfiati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
One of the important skills in the 21st century is the ability to think creatively, which is closely related to the concept of creativity. Low levels of student creativity are often caused by the use of learning methods, models and strategies that do not support the development of these abilities. This research aims to describe the real conditions of implementing a creative exploration project by utilizing upcycling waste into works of art using the STEAM and Tri N approaches, in order to increase student creativity. This research used a descriptive qualitative method with the research subjects being class V students, consisting of 4 male students and 10 female students. Data collection techniques include observation, interviews and documentation. Milles and Huberman data analysis techniques, which include data reduction, presentation and verification. The research results show that the waste upcycling project integrated with STEAM and Tri N is effective in developing elementary school students' creativity. In these four aspects, the score mode is 4. Score 4 has a percentage of 45%, score 3 is 33%, score 2 is 16%, and the lowest score is 6%. The development of creativity goes hand in hand with the implementation of innovative, creative and fun learning, because there is a significant relationship between the learning model used and increasing student creativity. This project-based approach integrates SBDP and IPAS lesson content.